Retinitis Pigmentosa: Genetics and Clinical Presentation - Ziauddin Ahmed Shaikh, Jamshed Ahmed, Aurangzeb Shaikh (Pakistan Journal of Ophthalmology, 2009)
Purpose: To evaluate clinical presentation and inheritance patterns in patients of retinitis pigmentosa. Material and Methods: This study was conducted in the department of Ophthalmology, Dow University of Health Sciences, Civil Hospital Karachi and Sindh Government Lyari Greneral Hospital Karachi from October 2002 to March 2008. Ophthalmic examination was performed on 112 patients and their family members to identify affected individuals and to characterize the disease phenotype. Family pedigree was obtained. Some family members also had fundus photographs and fluorescein angiography. Results: Legal blindness at the time of presentation was found in 104(46.4%) eyes while 76 (33.9 %) eyes have visual impairment. Visual field was constricted on confrontation in 44 (39.3%) cases. Regarding modes of inheritance, autosomal dominant was found in 5 (4.5%) autosomal recessive in 78(69.6%) and X-Linked in 7 (6.3%). Twenty two (19.6%) cases were sporadic. Typical retinitis pigmentosa picture was found in 97 (86.6%) while 15 (13.3 %) patients showed atypical picture in which 6 (5.35%) cases of pericenteric RP, 5(4.46%) cases of Usher’s syndrome and 2(1.78%) cases of retinitis punctata albescence. One case of Bardet-Biedl syndrome and one case of Cockayne's syndrome was found. Conclusions: There is a high prevalence of blindness among patients of retinitis pigmentosa. Autosomal recessive mode of inheritance is the most common. Blindness from retinitis pigmentosa can be prevented by early diagnosis and by motivating the patients to avoid cousin marriages.